Kualitas Pelayanan terhadap Kepuasan Pasien Rawat Inap saat Post Pandemi COVID-19 - Aji Bharata; Sulis Diana; Nurwidji Nurwidji; Dhonna Anggreni (Journal of Telenursing (JOTING), 2023)
This study aims to determine the Quality of Service on Inpatient Satisfaction during the Post Pandemic COVID-19 in the Arjuna Room of Kerta Usada Hospital. This research method is an analytical survey with an explanatory approach. The results showed that all independent variables of service quality, which included Reliability (X1=0.283), Responsiveness (X2=0.292), Assurance (X3=0.450), Empathy (X4=0.407), and Tangibles (X5=0.282) were significantly related to satisfaction inpatients. In conclusion, it shows that assurance has the most significant influence on patient satisfaction. Keywords: Patient Satisfaction, Service Quality, Post Pandemic